“Caracterización de la salud bucal de los adolescentes del centro de salud no. 1 riobamba, 2019” - Jessica Maritza, Oyasa Salan (2020)
The purpose of this study was to evaluate the oral health status and quality of life of adolescents with an age ranging from 12 to 19 years. They were treated at the health center No. 1 in Riobamba city from 2018 to 2019. The type of research was cross-sectional. The study population consisted of 400 adolescents, with a sample of 100, taking into account the selection criteria. Quantitative and qualitative variables were taken into account, including age, sex and quality of life. The research compared to the CPOD and IHOS index. One-hundred medical records analyzed, according to the IHOS of adolescents. Adolescents living with their father show their body images covered with a higher incidence of plaque and calculus, rather than those living with their mother or another relative. The adolescents with both parents with job instability, presented a greater number of lost pieces, the young people said they did not know if they would be accepted in society. They were the ones that presented the greatest amount of pieces with cavity processes, the body image of the adolescents had significant influence on the pieces with carious processes. The teenagers who live with another family member were the ones who lost the most dental pieces. The teenagers who did not have a life project were the ones who showed the most parts with carious processes.